ANALYSIS OF NYALI COMMUNITY (NYAMAN LITERASI) IN IMPROVING READING INTEREST AT SMPN 20 MEDAN: ANALISIS KOMUNITAS NYALI (NYAMAN LITERASI) DALAM MENINGKATKAN MINAT BACA DI SMPN 20 MEDAN - Yusri; Faisal Riza (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Education and literacy are key components in forming an intelligent and skilled generation, with students' reading interest being a crucial indicator of literacy ability. Comprehensive education encompasses the development of spirituality, personality, intelligence, and skills, as stated in Law No. 20 of 2003. The government strives to enhance literacy through the School Literacy Movement (GLS), which aims to cultivate and improve literacy comprehensively and sustainably. This study examines the efforts of the NYALI (Nyaman Literasi) community at SMPN 20 Medan in increasing students' reading interest. NYALI creates a supportive environment for reading through various activities such as Book Tourism, short story classes, public speaking classes, an English Club, library volunteers, and peer tutors. This research uses a qualitative approach with surveys, observations, and interviews to evaluate the impact of literacy activities on students' reading interest. The results show that student participation in NYALI activities has increased their confidence and academic performance. Internal factors like motivation and external factors such as family and school environment play crucial roles in students' reading interest. School literacy programs, supported by the community and family, are essential for creating a generation that loves reading and possesses strong literacy skills.